ARTIFICIAL INTELLIGENCE IS TRANSFORMING SOCIETY - Dr Humera Nuzhat (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
As with most changes in life, there will be positive and negative impacts on society as artificial intelligence continues to transform the world we live in. How that will balance out is anyone’s guess and up for much debate and for many people to contemplate. As an optimist at heart, I believe the changes will mostly be good but could be challenging for some. Here are some of the challenges that might be faced (and we should be thinking about how to address them now) as well as several of the positive impacts artificial intelligence will have on society. Artificial Intelligence (AI) is rapidly reshaping various aspects of society, from healthcare and education to business and governance. This research article explores the multifaceted impacts of AI on social structures, economic systems, and individual lives. We analyze both the potential benefits and challenges posed by AI, focusing on ethical considerations, employment implications, and the digital divide. Through a comprehensive review of existing literature and case studies, we aim to provide insights into how AI can be harnessed for societal benefit while mitigating its risks. Artificial intelligence (AI), known by some as the industrial revolution (IR) 4.0, is going to change not only the way we do things, how we relate to others, but also what we know about ourselves. This article will first examine what AI is, discuss its impact on industrial, social, and economic changes on humankind in the 21st century, and then propose a set of principles for AI. The IR1.0, the IR of the 18th century, impelled a huge social change without directly complicating human relationships. Modern AI, however, has a tremendous impact on how we do things and also the ways we relate to one another. Facing this challenge, new principles of AI must be considered and developed to provide guidelines for the AI technology to observe so that the world will be benefited by the progress of this new intelligence.